2004
DOI: 10.1002/art.20335
|View full text |Cite
|
Sign up to set email alerts
|

Etanercept treatment of psoriatic arthritis: Safety, efficacy, and effect on disease progression

Abstract: Objective. Etanercept has been shown to improve the articular and cutaneous manifestations of psoriatic arthritis (PsA). In this study, we further evaluated the safety, efficacy, and effect on radiographic progression of etanercept in patients with PsA.Methods. Patients with PsA (n ‫؍‬ 205) were randomized to receive placebo or 25 mg etanercept subcutaneously twice weekly for 24 weeks. Patients continued to receive blind-labeled therapy in a maintenance phase until all had completed the 24-week phase, then cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

25
536
1
24

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 811 publications
(586 citation statements)
references
References 29 publications
25
536
1
24
Order By: Relevance
“…However, failure of anti‐TNF treatment, loss of efficacy, and intolerance in some patients highlight the unmet need for new therapies with an alternative mechanism of action 12. The radiographic findings from this study are consistent with those from other trials of TNF and IL‐12/23 inhibitors involving anti‐TNF–naive populations 13, 14, 15, 16, 17 and suggest that IL‐17A may offer an additional therapeutic option for patients with PsA.…”
Section: Discussionsupporting
confidence: 76%
“…However, failure of anti‐TNF treatment, loss of efficacy, and intolerance in some patients highlight the unmet need for new therapies with an alternative mechanism of action 12. The radiographic findings from this study are consistent with those from other trials of TNF and IL‐12/23 inhibitors involving anti‐TNF–naive populations 13, 14, 15, 16, 17 and suggest that IL‐17A may offer an additional therapeutic option for patients with PsA.…”
Section: Discussionsupporting
confidence: 76%
“…Anti-tumor necrosis factor ␣ (anti-TNF␣) agents improve the arthritic and psoriatic manifestations of PsA (2)(3)(4). Golimumab is a new human monoclonal antibody against TNF␣ that binds with high affinity and specificity to soluble and transmembrane TNF␣ and has a median terminal half-life of ϳ2 weeks (5).…”
mentioning
confidence: 99%
“…There is some evidence of the link between inflammation and damage in PsA, where observational studies have shown that active inflammatory disease predicts future outcome (1). New therapies, such as the tumor necrosis factor ␣ blockers, have shown a reduction in disease activity and a corresponding reduction in radiographic progression of damage (2)(3)(4). Ongoing joint damage can cause significant functional impairment and disability, which raises the possibility that controlling disease activity could improve outcome.…”
Section: Introductionmentioning
confidence: 99%